Factors underlying international doctoral students’ English academic writing abilities - Wai Mar Phyo; Marianne Nikolov; Ágnes Hódi (PLoS ONE, 2025)
The ability to write academic texts in English requires both knowledge of academic writing conventions and expertise in academic discourse to address the needs and expectations of the target academic audience in respective disciplines (Hyland, 2018). This study investigates the relationship between non-native English-speaking doctoral students’ English academic writing abilities and various factors, including their English literacy background, research knowledge, ability to read and critically evaluate academic texts, coping with emotional challenges such as stress and anxiety, as well as feedback and motivation. A total of 255 international doctoral students, speaking 49 different first languages, participated in the study. Data were collected via a survey with items presented on a 1–6 Likert scale following Dörnyei and Dewaele (2022). The analysis revealed the significant impact of English literacy background, initial academic writing abilities, and research knowledge on students’ self-assessment of academic writing skills and research competence at the outset of their doctoral studies. While prior experience in academic writing proved beneficial, it did not always translate into significant improvements in current writing abilities or research knowledge at later stages. Feedback from advisors and doctoral research course instructors emerged as vital components in supporting academic reading and motivation throughout their doctoral journey. However, the quality of peer feedback appeared to have less impact on students’ academic performance and psychological state. Overall, these findings underscore the complexity of factors influencing academic writing and research competence among NNES doctoral students, suggesting the importance of tailored support and interventions to enhance their scholarly development.